Peranan Kemasan Untuk Meningkatkan Pemasaran UMKM Roti Al Batsit Kota Bengkulu - Efendi, Fithria habib; Hidayah, Nenden Restu; Susena, Karona Cahya (Universitas Dehasen Bengkulu, 2023)
UMKM Roti Al Batsit is a small business engaged in the food industry which is located in the city of Bengkulu. As one of the MSMEs, the challenge that must be faced is how to increase product sales and introduce the Roti Al Batsit brand to the public. Therefore, the community service program is entitled